2022
DOI: 10.26434/chemrxiv-2022-ql13w
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Crystallographic and Computational Analysis of Solid Form Landscape of Three Structurally Related Imidazolidine-2,4-dione Active Pharmaceutical Ingredients: Nitrofurantoin, Furazidin and Dantrolene

Abstract: We present a crystallographic and computational study of three hydantoin-based active pharmaceutical ingredients nitrofurantoin, furazidin, and dantrolene aimed at identifying factors resulting in different propensities of these compounds to form polymorphs, hydrates, solvates, and solvate hydrates. This study is a continuation of our research towards understanding how small structural differences in closely related compounds affect their propensity to form different crystal phases, as all three compounds cont… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Likewise, for solvates in which solvent is mainly a void filler, the packing efficiency is not always higher than that in the nonsolvated form, and the solvent size, shape, and the intermolecular interactions often determine the solvent selectivity . In contrast, if the solvent is situated in large structure voids, it can have almost no effect on the structure of the host framework, and the properties or the size of the solvent can have minimal to no role in discrimination of what solvents can be included in the structure, as, for example, observed for the clathrates of deoxycholic, cholic, and apocholic acids. , Detailed studies of the highly similar solvates of 3,5 dihydroxybenzoic acid and apremilast solvates and cocrystals, however, have shown that differences in the host framework present in different phases can be identified and linked with the properties of the solvent (or coformer).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, for solvates in which solvent is mainly a void filler, the packing efficiency is not always higher than that in the nonsolvated form, and the solvent size, shape, and the intermolecular interactions often determine the solvent selectivity . In contrast, if the solvent is situated in large structure voids, it can have almost no effect on the structure of the host framework, and the properties or the size of the solvent can have minimal to no role in discrimination of what solvents can be included in the structure, as, for example, observed for the clathrates of deoxycholic, cholic, and apocholic acids. , Detailed studies of the highly similar solvates of 3,5 dihydroxybenzoic acid and apremilast solvates and cocrystals, however, have shown that differences in the host framework present in different phases can be identified and linked with the properties of the solvent (or coformer).…”
Section: Introductionmentioning
confidence: 99%
“…Solvate hydrates are mostly observed for prolific formers of solvated phases, for example, bosutinib 8 and olanzapine, 9,10 and are usually formed with highly polar solvents. 7 Among other compounds of pharmaceutical interest, nevirapine, 11 atorvastatin calcium, 12 cholic acid, 13,14 deoxycholic acid, 15,16 furazidin, 17,18 and dantrolene 19 have structurally characterized solvate-hydrates. The size and shape of all of these molecules, except for furazidin and dantrolene, prevent efficient packing, resulting in formation of structures with cavities, and/or allow to achieve efficient hydrogen bonding only in structures with reduced packing efficiency.…”
Section: Introductionmentioning
confidence: 99%